Handbook of Ethical Foundations of Mindfulness (Mindfulness in Behavioral Health, 2018)
This handbook explores the multifaceted ethical dimensions of mindfulness, from early Buddhist sources to present-day Western interpretations of mindfulness. It takes a modern ethical approach to the study of mindfulness, and traces contemporary mindfulness practice from solitary journey to the global whole. Noted practitioners, teachers, scholars, and other professionals lend diverse perspectives to the debate over the moral content of mindfulness and its status as religious, secular, or post-secular practice. Chapters offer new views on the roots of mindfulness in Buddhist moral teachings, ethical mindfulness in interpersonal relationships, and the necessity of ethics in mindfulness-based education and therapy. Chapters also discuss current debates concerning the ethics of mindfulness across the applied fields of education and pedagogy, business, economics, and the environment. Topics featured in this handbook include: · Mindfulness as the true foundation of a naturally ethical life. · Mindfulness and its impact on emotional life, interpersonal relationships, and forgiveness. · How Buddhist ethics informs spiritual practice across the three main vehicles (yanas) of Buddhism and its relation to mindfulness. · "McMindfulness", or the mass marketization and commodification of mindfulness-based interventions (MBIs). · How an ethic of interdependence formed by Buddhist principles and mindfulness practices can help address the environmental crisis. The Handbook of Ethical Foundations of Mindfulness is a must-have resource for researchers, clinicians/professionals, and graduate students in psychology, complementary and alternative medicine, and social work as well as occupational and rehabilitation therapy, nursing, philosophy, business management, and teachers of Buddhism and meditation.